ANALISIS KESESUAIAN LAHAN UNTUK PENGEMBANGAN BUDIDAYA IKAN BUBARA (Caranx sp) PADA KERAMBA JARING APUNG DI PERAIRAN TELUK AMBON DALAM - Fitriah, Rizkah; Tuhumury, Semuel F; Sahetapy, Dicky (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2023)
The development of awuaculture is significantly influenced by land suitability analysis. This research was conducted from May 2021-April 2022 in Inner Ambon Bay (IAB). This study aims to analyse physical, chemical and environmental factors, suitability and carring capacity of Bubara (Caranx sp) fish farming with Floating net Cages (FNC) system in Inner Ambon Bay. Physical and chemical environmental data were measured in-situ, and the land suitability matrix based on a weighting system was used to analyse the environmental suitability and carring capasity for awuaculture development. The IAB waters have potential for Bubara farming using bery suitable and suitable FNS System. The development of bubara aquaculture with FNC system in IAB waters is in two classes, very suitable to the area range of 1046,30-1113,32 ha and suitable to the area range of 2,25-65,68 ha depending on the season. The carring capacity of the land for placing FNC in the fish farm bubara is about 1.667 units in the west season, about 1.669 units in the transition season I, about 1.670 units in the eastern season and about 1.673 units in the second transition season II. The carring capacity of highly suitable land (waters) is higher (1.568-1.670 units) than that of suitable land (3-98 units). Some of the activities that can reduce the carring capacity of the IAB aquatic environment for fish farming with the FNC are industrial and ship waste disposal, garbage, coastal reclamation, sedimentation, agricultural waste and waste from microorganisms. ABSTRAK Analisis kesesuaian lahan sangat berperan penting dalam pengembangan budidaya perairan. Penelitian ini berlangsung pada bulan Mei 2021-April 2022 yang berlokasi di perairan Teluk Ambon Dalam. Tujuan penelitian ini yaitu menganalisis faktor-faktor lingkungan fisik, kimia, serta kesesuaian dan daya dukung lahan untuk budidaya ikan bubara (Caranx sp) dengan sistem KJA di perairan Teluk Ambon Dalam. Data lingkungan biofisik diukur secara insitu, dan matriks kesesuaian lahan berdasarkan sistem pembobotan digunakan untuk menganalisis kesesuaian dan data dukung lingkungan untuk pengembangan budidaya. Perairan Teluk Ambon Dalam memiliki potensi untuk budidaya ikan bubara dengan sistem KJA yang Sangat Sesuai dan Sesuai. Pengembangan budidaya ikan bubara dengan sistem KJA di perairan TAD berada pada dua kelas yaitu Sangat Sesuai dengan kisaran luasan berkisar 1046,29-1113,32 ha, dan kelas Sesuai dengan luasa berkisar 2,25-65,68 ha berdasarkan musim. DAya dukung lahan untuk penempatan KJA dalam budidaya ikan bubara pada musim barat sekitar 1.667 unit, pada musim peralihan I sekitar 1.669 unit, pada musim timur sekitar 1.670 unit, dan pada musim peralihan II sekitar 1.673 unit. Daya dukung lahan (perairan) kelas Sangat Sesuai lebih besar (1.568-1.670 unit KJA) dibandingkan dengan daya dukung lahan dengan kelas kategori Sesuai (3-98 unit KJA. Beberapa aktivitas yang dapat menurunkan daya dukung lingkungan perairan TAD untuk budidaya ikan dengan sistem KJA adalah limbah industri dan pembuangan limbah kapal, sampah, reklamasi pantai, sedimentasi, limbah pertanian, dan limbah mikroorganisme. Kata Kunci: Pengembangan, kesesuaian, daya dukung, keramba jaring apung, Teluk Ambon Dalam